Mulan - Cook, Barry; Bancroft, Tony (b, 1999)
Based on an ancient Chinese poem, the legend of MULAN beautifully unfolds in Disney's 36th animated classic! Full of daring adventure, hilarious characters and inspiring music, this new Special Edition celebrates honor, courage and a young girl's quest to be true to her own hearts. Beautiful and clever Mulan proves her worth outside of her traditions-bound society when, disguised as "Ping," she bravely takes her father's place in the Imperial Army. Helped by her outrageously funny guardian dragon Mushu and a lucky cricked named Cri-Kee, Mulan strives to earn the respect of her fellow warriors and their handsome Captain Shang. A climactic battle atop the Imperial Palace is where her family's honor and the fate of the Emperor and all of China rest in her hands! MULAN is a one-of-a-kind film about a one-of-a-kind heroine. As the Emperor says, " You don't find a girl like that in every dynasty!" Your whole family will enjoy experiencing Mulan's legendary journey!